Production and evaluation of an instructional video for teaching writing to children with attention deficit hyperactivity disorder - Ang, Maria Teresa P. (2009)
This research produced and evaluted an instructional video for teaching writing to children with ADHD. The video consisted of four animations: memonics as story parts reminder, a practice story, and two stories for writing compositions. These were shown to children with ADHD aged 9-12 years. After viewing, they were asked to write a short story about each video. It was found that the research video as a form of computer technology for teaching writing inititated social skills among children with ADHD. It can bring high on-task behavior and high attention span during the writing tasks but was not able to bring observable improvement in the writing skills of children with ADHD. The supplied mnemoics as a story parts reminder was more evident in oral context than in written contexts as shown in the discussion and writing activity.